ANALISIS PENGENDALIAN INTERN PERSEDIAAN BARANG DAGANG PADA PT. PANCA KURNIA NIAGA NUSANTARA MEDAN - Fanny Angkasa; Edison Sagala; Elidawati Elidawati (JURNAL BISNIS KOLEGA, 2019)
Abstract. This research was conducted at PT. Panca Kurnia Niaga Nusantara Medan. As a company engaged in the distributor of fertilizer and agrochemical products, companies must have good internal control of merchandise inventory. Internal control can be said to be good if it has been implemented in accordance with the COSO (Committee of Sponsoring Organizations). The purpose of this study is to find out and analyze internal controls at PT. Panca Kurnia Niaga Nusantara Medan.This type of research is a descriptive research with a case study at PT. Panca Kurnia Niaga Nusantara Medan is by analyzing the internal control of merchandise inventory at PT. Panca Kurnia Niaga Nusantara Medan.Based on the results of the study indicate that most activities and documents relating to merchandise inventory and internal control of merchandise inventory are sufficiently in accordance with the Committee of Sponsoring Organizations (COSO) but still require a little change to improve the accuracy of employee and the separation of duties that are still need to be applied in the company. Keywords: Internal Control, Merchandise Inventory.